POLA PENGAMBILAN KEPUTUSAN RUMAH TANGGA DAN ADOPSI INOVASI DALAM KEGIATAN USAHATANI PADA BEBERAPA SPESIFIK SOSIOBUDAYA PETANI DI PROPINSI LAMPUNG - Hasanuddin, Tubagus (Universitas Sebelas Maret, 2004)
The succesfull of development agriculture cannot be participation of farmer, included in pattern of decision making in farmer family and adoption of innovation. Therefore, research to pattern of decision making of farmer family and adoption of innovation from various specific socioculture is important. This research done in five countryside in Kecamatan Gedong Tataan, Kabupaten Lampung Selatan, and Kata Bandarlampung, Propinsi Lampung. This research done since July 2004 - September 2004. This research done by using approach survey, and technique of sample with Multy stage stratified random sampling . Data analysis done by using statistic non parametric (Uji n Sampel Bebas Kruskall- Wallis Analysis and Gamma and Sommers Corelations). The result of research is: (I) pattern of decision making of farmer family from Jawa, Sunda and Lampung sosioculture are husband dominant ,(2) pattern ofdecision making of farmer family from Jawa, Sunda and Lampung sosioculture are different; (3) adoption innovation in farm shape from Jawa, Sunda, Lampung are not different; (4) pattern of decision making of farmer family not related with adoption innovation; and (5) Socioculture and farm shape have related with pattern of decision making of farmer family.